2021
DOI: 10.1001/jamainternmed.2021.2959
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 Reinfection 1 Year After Primary Infection in a Population in Lombardy, Italy

Abstract: This cohort study examines the rate of SARS-CoV-2 reinfection among people in Lombardy, Italy, who previously recovered from COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 6 publications
8
98
3
1
Order By: Relevance
“…Prolonged viral replication in immunocompromised hosts may favor the generation and selection of nAb escape mutants, which in turn drives Ab affinity maturation and eventually enhanced neutralization breadth and potency [ 223 ]. In humans, previous SARS-CoV-2 infection and anti-spike Ab seropositivity significantly reduce the risk of SARS-CoV-2 reinfection [ 215 , 224 , 225 , 226 , 227 , 228 , 229 ], which is in line with vaccination outcome analyses [ 230 , 231 , 232 , 233 , 234 , 235 , 236 ] altogether implying that SARS-CoV-2 binding and/or nAbs exert protective effects. Consequently, neutralization levels have been found highly predictive of immune protection with seven current vaccines and in convalescent cohorts, and provide an evidence-based model of SARS-CoV-2 immune protection [ 237 ].…”
Section: Humoral Immune Responsessupporting
confidence: 61%
“…Prolonged viral replication in immunocompromised hosts may favor the generation and selection of nAb escape mutants, which in turn drives Ab affinity maturation and eventually enhanced neutralization breadth and potency [ 223 ]. In humans, previous SARS-CoV-2 infection and anti-spike Ab seropositivity significantly reduce the risk of SARS-CoV-2 reinfection [ 215 , 224 , 225 , 226 , 227 , 228 , 229 ], which is in line with vaccination outcome analyses [ 230 , 231 , 232 , 233 , 234 , 235 , 236 ] altogether implying that SARS-CoV-2 binding and/or nAbs exert protective effects. Consequently, neutralization levels have been found highly predictive of immune protection with seven current vaccines and in convalescent cohorts, and provide an evidence-based model of SARS-CoV-2 immune protection [ 237 ].…”
Section: Humoral Immune Responsessupporting
confidence: 61%
“…Long-lived bone marrow plasma cells speci c to SARS-CoV-2 have been detected in the bone marrow of recovered COVID-19 patients, serving as a persistent and essential source of antibodies [27]. A clinical study showed that reinfection was rare 1 year after primary infection, likely due to the protective effect of natural infection [28]. Nevertheless, there are limited data on whether protective immunity induced by natural infection with one strain of SARS-CoV-2 can confer cross-protection against variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended bibliography: [61][62][63][64][65] • SARS-CoV-2 reinfection remains an overall infrequent event.…”
Section: Sars-cov-2 Reinfection Vs No Reinfectionmentioning
confidence: 99%
“…Reassuring data have accrued since, with several works supporting humoral immune responses to SARS-CoV-2 for at least 5-7 months [603,604] and immunological memory (especially T-cell mediated) for at least 6-8 months [605]. Epidemiological analyses have reported natural immunity protection from reinfection for at least 6-12 months [61,64,604,606,607]. Protection could go beyond these estimates because of the complexity and robustness of immune responses, though it is also acknowledged that the induction and durability of immune responses-both humoral and cellular-are heterogenous across individuals and may be shorter in some [608].…”
Section: Reinfection and Natural Immunitymentioning
confidence: 99%